2019
DOI: 10.3390/catal9070619
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Bound PAH Residues in Contaminated Soils by Fenton Oxidation

Abstract: The availability of bound residues of polycyclic aromatic hydrocarbons (PAHs), in reference to their parent compounds, can be enhanced by microbial activity and chemical reactions, which pose severe risks for the ecosystems encompassing contaminated soils. Considerable attention has been raised on how to remove these bound residues from PAH-contaminated soils. This paper provides a novel application of Fenton oxidation in the removal of bound residues of model PAHs, such as naphthalene (NAP), acenaphthene (ACP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 57 publications
1
6
0
Order By: Relevance
“…Previous studies have shown that the biochar prepared at lower temperatures (<400 • C) has more un-carbonized organic residues such as polycyclic aromatic hydrocarbons [52]. These organic residues might compete with the target pollutant (ciprofloxacin) for the consumption of reactive species [53]. The BC600 biochar alone can remove more ciprofloxacin, according to the results in Figure 8a.…”
Section: The Biochar's Influence To the Removal Of Ciprofloxacinmentioning
confidence: 79%
“…Previous studies have shown that the biochar prepared at lower temperatures (<400 • C) has more un-carbonized organic residues such as polycyclic aromatic hydrocarbons [52]. These organic residues might compete with the target pollutant (ciprofloxacin) for the consumption of reactive species [53]. The BC600 biochar alone can remove more ciprofloxacin, according to the results in Figure 8a.…”
Section: The Biochar's Influence To the Removal Of Ciprofloxacinmentioning
confidence: 79%
“…The CAs have a strong chelation ability for metal ions to keep them in solution even at higher pH values which extends the optimum range of reaction pH. As illustrated in Table 2, chelating agents have been used in Fenton oxidation of various pollutants such PAHs (Laurent et al, 2012;Lemaire et al, 2019;Liao et al, 2019;Zhao et al, 2019), TPHs (Chunyang et al, 2019;Liu et al, 2019;Martínez-Pascual et al, 2015;Sutton et al, 2014b;2014a;Wang et al, 2015;Xu et al, 2011a;2011b;2017a; or polychlorinated biphenyls (PCBs) (Ma et al, 2018). The use of CAs with soluble Fe(II) exhibited significant enhancement in oxidation efficiency.…”
Section: Modified Fenton Oxidation and Role Of Chelating Agentsmentioning
confidence: 99%
“…7The compressive work and viscous dissipation effects of liquid are negligible. (8) The effects of contaminants are ignored.…”
Section: Model Of Heating Fieldmentioning
confidence: 99%
“…A cornucopia of remediation technologies has been developed to treat contaminated soils [5][6][7][8]. Among these technologies, in situ soil thermal remediation holds an important niche role due to its ability to clean pollutants quickly and reliably [9].…”
Section: Introductionmentioning
confidence: 99%